2014
DOI: 10.5539/gjhs.v6n7p124
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fish Oil Capsules and Vitamin B1 Tablets on Duration and Severity of Dysmenorrhea in Students of High School in Urmia-Iran

Abstract: Aims:The purpose of this study is the comparison of the effect of vitamin B1 and fish oil with together on severity and duration of dysmenorrhea, and if it is effective, we can administrate both of them with less complication to compare with other chemical drugs which has many disadvantages.Study Design:High school of Urmia city, between March 2008 and June 2008.Methodology:This study has a double-blind clinical trial design.240 high school female students with dysmenorrhea by a randomized Method were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 8 publications
1
30
0
9
Order By: Relevance
“…Previous studies have identified that fish oils may present protective factors against menstrual pain [ 49 , 50 ]. In line with our results, a previous study carried out among Spanish university women identified a lower proportion of women with primary dysmenorrhea among those who always cooked with olive oil [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that fish oils may present protective factors against menstrual pain [ 49 , 50 ]. In line with our results, a previous study carried out among Spanish university women identified a lower proportion of women with primary dysmenorrhea among those who always cooked with olive oil [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Zafari et al, 39 vitamin B1 was compared with ibuprofen and it was reported that there was no significant difference in pain reduction between the two groups, but due to its poor side effects, use of vitamin B1 was recommended. In a study by Hosseinlou et al, 40 vitamin B1 group alone, fish-oil capsule group, mix of vitamin B1 and fish oil group finally all three groups were compared with placebo group and it was reported that there was a significant reduction in pain severity for all treatment groups.…”
Section: Vitamin B1mentioning
confidence: 99%
“…Adanya hubungan antara konsumsi asam lemak omega-3 dengan tingkat dismenore sesuai dengan penelitian yang dilakukan oleh Hosseinlou dan kawan-kawan di Iran tahun 2008 menyatakan bahwa asam lemak omega-3 berperan dalam mengontrol rasa nyeri. 18 Penelitian lain yang dilakukan oleh Bente dan kawan-kawan juga menyatakan bahwa asam lemak omega-3 berperan dalam mengontrol rasa nyeri. Peran regulasi dari asam lemak omega-3 terhadap sakit peradangan terkait dengan rheumathoid artritis, dismenore dan penyakit usus inflamasi.…”
Section: Pembahasanunclassified